Experimental study of the anisotropic thermal conductivity of 2D carbon-fiber/epoxy woven composites. (1st July 2021) - Zhang, Hu; Wu, Kefan; Xiao, Guangming; Du, Yanxia; Tang, Guihua
Abstract: The anisotropic micro-structure of fiber will lead to the macroscopic anisotropic properties of fiber reinforced composites in both heat transfer and mechanical strength. However, few experimental studies have be made on the anisotropic heat transfer properties of fiber reinforced composites. In this study, the anisotropic thermal conductivities of two-dimensional (2D) plain woven and twill woven carbon-fiber/epoxy composites are measured at different temperature with the one-dimensional (1D) steady-state method, transient plane source (TPS) method and transient hot wire method, respectively. The out-of-plane thermal conductivity and in-plane thermal conductivity at the temperature ranging from −45 °C to 160 °C are obtained and comparisons are made among the three methods. The results show that all the three methods can be used to measure the anisotropic thermal conductivity of fiber/epoxy woven composites. Both the out-of-plane thermal conductivity and in-plane thermal conductivity of carbon-fiber/epoxy woven composites increase with temperature, and the in-plane thermal conductivity is approximately four times as high as the out-of-plane thermal conductivity for the plain woven composites. Compared with the results of 1D steady-state method, the max deviations of TPS method and hot wire method are 18.1% and 17.1%, respectively. The sources of error that leading to the deviations are also discussed.